Pembentukan Karakter Islami Pada Peserta Didik Melalui Pendekatan Budaya Di SDN Sarude, Kecamatan Sarjo, Kabupaten Pasangkayu - Magfirah; Asman Deeteng; Naima; Adawiyah; Erniati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Islamic character education is a fundamental aspect of Islamic Religious Education in elementary schools because it serves as the foundation for the formation of students' personalities from an early age. This study aims to describe the process of Islamic character formation in students through a cultural approach at SDN Sarude, Sarjo District, Pasangkayu Regency, which has a multi-ethnic socio-cultural background. The study used a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. Research informants included the principal, Islamic Religious Education teachers, class teachers, and students. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Islamic character formation at SDN Sarude is carried out holistically and sustainably through the integration of local Mandar cultural values, the habituation of religious activities, teacher role models, and support from the social environment. Mandar cultural values ​​such as sipakatau, sipakalebbi, and sipakaingge are integrated into Islamic Religious Education (PAI) learning and have proven effective in instilling Islamic values ​​such as empathy, respect, and social responsibility. The habituation of religious activities such as communal prayer, dhuha prayer, Al-Qur'an recitation, and socio-religious activities strengthen the internalization of religious values ​​and social awareness of students. Teacher role models are a dominant factor that encourages the success of character education, while the religious community environment strengthens the continuity of values ​​between school and social life. This study concludes that Islamic character education rooted in local culture and supported by synergy between schools and the community is effective in forming students who are religious, have noble morals, and are cultured